Level of Creative Thinking Among Prospective Chemistry Teachers - Apriwanda, W.; Hanri, C. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Creative thinking is one of the skills considered in facing the 21st-century era. Similar to other science domains, creative thinking is also crucial in chemistry learning. The variety of problems in chemistry makes students must be creative thinkers to solve chemistry problems faced. In the classroom, a chemistry teacher has a role in encouraging students’ creative thinking. Other than that, this role also applies to prospective chemistry teachers who will have the same responsibility in the future. Therefore, this study aims to identify the level of creative thinking among prospective chemistry teachers, and identify the aspect of creative thinking that needs to improve. The research design used in this study was a quantitative approach with descriptive research. There were 92 prospective chemistry teachers in Pekanbaru, Riau-Indonesia selected using simple random sampling. Data were collected using open-ended questions and analyzed using the rubric of scoring. Once scoring was done, the score obtained was presented in form of a percentage of score to determine the level of creative thinking. The finding reveals that the level of creative thinking of prospective chemistry teachers was moderate (percentage score of 35.43). The prospective chemistry teachers were at a low level of flexibility and fluency with a percentage score of 27.29 and 27.42 respectively. This finding could be a consideration for any stakeholder to improve the quality of education by taking steps to improve creative thinking among prospective chemistry teachers. With the hope, that none of the students in the future found is at a low level of creative thinking because the students have been taught by competent teachers.